Analysis of the Proliferation of Prophecy and Fake Prophets in Southwestern Nigeria: Implications and Policy - Adabembe, Kehinde Oluwatoyin (Advances in Social Sciences Research Journal, 2025)
Christianity has been a moral bastion of the African continent since it was introduced to the shore of Africa. It has impacted the continent regarding education, health, and agriculture. Meanwhile, it is unfortunate that the growth and development of the church in South-Western Nigeria have brought in some distasteful acts introduced by dubious pastors, prophets, and prophetesses. It is a fact that some pastors and prophets in Nigeria are politicizing prophecy. Thus, some people no longer believe in prophecy and prophetic utterances from some acclaimed Prophets and Prophetesses in Nigeria. It is worrisome that the actions of these pastors have led to the commercialization and politicizing of prophecy in the country. Against this background, this paper examined Analysis of the Proliferation of Prophecy and Fake Prophets in Southwestern Nigeria: Implications and Policy. A survey research method was used to assess this situation, and empirical results were found. From these results, it was discovered that there is confusion among the Christians in South-Western Nigeria because of different prophecies on a particular issue from prophets and prophetesses. Also, most people who call themselves prophets in the country are only looking for a livelihood. Moreover, unlike the biblical prophets, some contemporary prophets are moved by what they see, not what we have heard from God. It was also discovered that prophecy had lost the values attached to it in the past. The paper, therefore, recommends that a body coordinate and regulate prophecy and prophetic utterances in the country. Also, fake prophets must be identified and disciplined to bring sanity to Christendom.